Chronic heart failure and aging – effects of exercise training on endothelial function and mechanisms of endothelial regeneration: Results from the Leipzig Exercise Intervention in Chronic heart failure and Aging (LEICA) study. (March 2016) - Sandri, Marcus; Viehmann, Manuel; Adams, Volker; Rabald, Kristin; Mangner, Norman; Höllriegel, Robert; Lurz, Philipp; Erbs, Sandra; Linke, Axel; Kirsch, Katharina; Möbius-Winkler, Sven; Thiery, Joachim; et al.
Background: A reduction in number and function of endothelial progenitor cells (EPCs) occurs in both physiologic aging and chronic heart failure (CHF). We assessed whether disease and aging have additive effects on EPCs or whether beneficial effects of exercise training are diminished in old age. Methods: We randomized 60 patients with stable CHF and 60 referent controls to a training or a control group. To detect possible aging effects we included subjects below 55 (young) and above 65 years (older). Subjects in the training group exercised four times daily at 60% to 70% of VO2 max for four weeks under supervision. At baseline and after the intervention the number and function of EPCs were assessed. Results: As compared with young referent controls, older referent controls showed at baseline a reduced EPC number (young: 190 ± 37 CD34/KDR positive cells/ml blood; older: 131 ± 26 CD34/KDR positive cells/ml blood; p < 0.05) and function (young: 230 ± 41 migrated cells/1000 plated cells; older: 185 ± 28 cells/1000 plated cells; p < 0.05). In young and older CHF patients EPC-number (young: 85 ± 21 CD34/KDR positive cells/ml blood; older: 78 ± 20 CD34/KDR positive cells/ml blood) and EPC-function (young: 113 ± 26 cells/1000 plated cells; older: 120 ± 27 cells/1000 plated cells) were impaired. As a result of exercise training, EPC function improved by 24% in older referent controls ( p < 0.05), while it remained unchanged in young training referent controls and controls respectively. In young and older patients with CHF four weeks of exercise training resulted in a significant improvement in EPC numbers and EPC function (young: number +66% function +43%; p < 0.05; older: number +69% function +36%; p < 0.05). These results were accompanied by a significant increase in flow mediated dilatation in the training groups of young/older CHF patients and in older referent controls. Conclusions: Four weeks of exercise training are effective in improving EPC number and EPC function in CHF patients. These training effects were not impaired among older patients, emphasizing the potentials of rehabilitation interventions in a patient group where CHF has a high prevalence.